Degrowth is essential to achieve and sustain global net zero emissions - Martin John Bush (Multidisciplinary Adaptive Climate Insights, 2024)
For greenhouse gas emissions to remain at a sustainable condition of net zero after 2050, global mean per capita emissions must be held constant at close to 2 tonnes of carbon dioxide equivalent. The relationship between economic growth and greenhouse gas  emissions is examined by employing a modified Kaya Identity which shows that GDP and emissions are linked through an Emission Intensity Factor that declines asymptotically to a minimum value of approximately 50 gCO2e/$GDP. In high-income countries, if a condition of net zero emissions is to be maintained, per capita GDP must decline to a point significantly below the current mean value for high-income countries. Carbon inequality in Europe and USA is disaggregated by income cohort to demonstrate that under conditions of sustainable net zero emissions, the bottom 50 percent of the distribution can increase their share of GDP, but the middle 40 percent and the top 10 percent of the distribution must substantially reduce their per capita emissions. In particular, the top ten percent, who are disproportionately responsible for most of the negative environmental impacts associated with economic growth, must reduce their per capita GDP  by over 70 percent in the case of Europe and the USA.   Received: 01 October 2024 Accepted: 15 November 2024 Published: 12 December 2024